Tell it to me singing : a novel - Ramírez, Tita (Marysue Rucci Books, 2024)
"A Cuban American family is sent into a tailspin when the ailing matriarch confesses the first of several shocking secrets to her daughter before undergoing heart surgery in this tender and twisty debut novel"--